PENGGUNAAN KONSELING KELOMPOK REALITAS DALAM MENINGKATKAN SELF-REGULATED LEARNING MAHASISWA DIII KEPERAWATAN AKADEMI KESEHATAN RAJEKWESI BOJONEGORO - Agus Ari Afandi, Agus Ari Afandi (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
Vocational nursing education system balanced between theory and practice mastery requires students to have independence  in learning.The goal of this study was to test the effectivity of the use of group counseling in improving the reality of self - regulated learning  Diploma III Nursing students at the Academy of Health Rajekwesi Bojonegoro .  The system of reality counseling is want, direction, evaluation, plan.This study was a quasi experiment to study the type of non - randomized pretest - posttest design . Methods of data collection is purposive random sampling, questionary using a scale developed by Restu Diah Ayu ( 2010) to determine the self - regulated learning  students . These subjects are 16 D III nursing students Academy of health  Rajekwesi Bojonegoro who has self-regulated learning is low and very low categories . Data analysis techniques in this study using SPSS 16 for windows by using the Wilcoxon Mann Whitney test . Results of significance 0.002 < 0.05 then H0 is rejected and H1 is accepted . So use reality group counseling can improve self - regulated learning in nursing students D III Academy of Health Rajekwesi Bojoneogoro  . Keywords:reality group counseling, self regulated learning